Índice de governança sustentável: processos que ampliam a capacidade de governo - o caso de Catanduva, Sp - Sanches, Maria Cristina Pinheiro Machado (2019)
This research proposes to develop the Sustainable Governance Index (IGS), with concentrated and detailed variables in the processes of elaboration, implementation and management of public policies, under the three levels of the Carlos Matus Governance Triangle - project, governance and capacity; as well as to ensure the involvement of the population in the daily routine of municipal public management. In this way, the IGS serves as an evaluator of public policy processes by governance (public power, private initiative and community), as well as guiding guideline procedures. This is a methodological research that seeks the construction of an index that is capable of evaluating and guiding urban governance. That is, the present research is permeating the constant doubt: "How can we evaluate, monitor, direct, guide and promote urban governance?". The thesis aims at variables of procedures, knowledge, relations and actions, among others, that can influence the success of governance processes, following the principle of democratic management of cities and involving actors in responsibilities and rights, taking advantage of latent synergies. In this, the variables that make up the IGS are selected from the development of the chapters. Firstly, a bibliographical review on the public sphere and governance is carried out, from which the stages of governance and social participation from the most primary to the supposedly more developed, according to the variables that characterize it, are categorized. Then some of the documents that deal with the themes "right to the city" and "environmental balance" are studied: "Cities Charter", "New Urban Agenda" and "Sustainable Development Objectives" (ODS). From this study it was possible to identify common approaches between them. In the same way, the strategies used by public policy observatories as social control of results and means are studied; as well as to motivate municipal management to set public policy agendas to achieve goals and objectives. These strategies are related to the variables of the desired governance stage. Thus, the IGS methodology is designed. The common approaches identified in the documents studied are organized in 5 dimensions; whose cut of the IGS is established in the dimension here titled "Participatory and inclusive governance". The variables that make up the IGS are selected from these approaches related to governance strategies. Of the variables selected, the municipal urban governance evaluation questionnaire was composed of 92 indicators, organized in 27 blocks and 5 axes. Each indicator is a question that composes the questionnaire. In the proposed methodology the system of qualitative and quantitative evaluation of the answers is developed. From then on the IGS is applied in Catanduva, SP, as a case study. In this city the key actors and public and civil managers of public policies are identified, especially those policies geared towards the territorial and environmental physical environment. From the sample size study by the bibliographic recommendation, 68 questionnaires were applied. Parallel to this and still related to the variables of the IGS are analyzed the implementation, change and management flows of some documents - such as the Government Plan of the last two municipal administrations and the Participatory Master Plan of 2006; as well as emerging public policies in the city at the time of the survey. From the results of the application of the IGS questionnaire it was possible to identify intervals of governance excellence from the variables selected for this index and eminent vulnerabilities in the municipal governance processes; especially on the issues surrounding the governance of the system. As well as verifying the fragility of the public policies studied, the insufficiency of social control and the bureaucratization of the participation of the population, among others. In the application of the questionnaire, the lowest results achieved relate to the governance of the system; mainly in the production and dissemination of knowledge. It is expected that the continuous application of the IGS in the cities will assist in the orientation and implementation of the governance processes; but also allows greater transparency and access of society to municipal public management, and is an instrument capable of developing local capacities of technicians and community.